Pengaruh Penggunaan Whatsapp Terhadap Hasil Belajar Siswa pada Mata Pelajaran TIK di SMAN 1 Koto Baru - Junita, Norma Cahya; Zakir, Supratman (Indonesian Research Journal on Education, 2022)
Learning to use WhatsApp media in the form of an unstable network connection, allowing students to be late in sending their assignments. Students sometimes do not focus on learning because they are busy opening other applications. Students sometimes do not understand the learning material given by the teacher because of the lack of explanation given by the teacher. As a result of students not understanding the learning material, it also has an impact on student delays in collecting the given assignments and on the results of daily tests students do not reach the KKM. The sampling technique is non-probability sampling with purposive sampling type. Purposive sampling is a sampling technique that is considered by researchers when taking samples with characteristics. The type of research used is correlational. Correlational research is aresearch conducted to determine the relationship of a variable with other variables. The type of research instrument is a questionnaire or questionnaire. To test the data using SPSS 22. The technique of filling in the data is using a questionnaire. The tests carried out were validity, reliability, normality test, linearity test, hypothesis testing and R square test to see the effect of using WhatsApp on student learning outcomes. Theresult of the value of sig. (2-tailed) each variable X and Y that is <0.05. Judging from the value of rcount > rtable, the rtable value is 0.312. For the results of the reliability test, the X variable has Cronbach's alpha > 0.06. The value of X variable is 0.653 so it is said to be reliable. This shows that the instrument is in the form of a questionnaire that can be used to determine the effect of variable X. After processing, the R2 value is0.765, which means that the variable using WhatsApp has a strong influence on student learning outcomes or 76.5%.